Pengaruh Pupuk Daun Terhadap Pertumbuhan Bibit Kompot Anggrek Dendrobium Hasil Silangan - Lisa Erfa; Ferziana Ferziana; Raida Kartina (Politeknik Negeri Lampung., 2010)
The objective of this second year research was to find foliar fertilizer in stimulating the growth of community pot seedling of Dendrobium which was cross pollinated on the first year. The research was conducted in a Completely Randomaized Design with 11 treatmets and 4 replication. The treatments were: vitabloom (P1), gandasil D (P2), plant catalyst (P3), dekastar (P4), red hyponex (P5), vitabloom+dekastar (P6), vitabloom+red hyponex (P7), gandasil D+dekastar(P8), gandasil D+red hyponex P(9), plant catalyst+dekastar (P10), plant catalyst+red hyponex (P11). The results showed that (1) Vitabloom (VB) application gave a better growth of dendrobium seedling (fresh weight, colour and vigor), followed by vitabloom combined with dekastar (VB DS), and dekastar (DS); (2) Plant catalys (PC) gave the lowest growth of seedling, otherwise, combined with red hyponex (PC HM); and (3) Applicaton of higher N content fertilizers (vitabloom, and dekastar or its combination) showed a better and faster growth of seedling compared with applicaton of lower N content fertilizers (plant catalyst). Keywords:Dendrobium seedling, foliar fertilizer, pertumbuhan